Preliminary clinical study of the safety of hepatectomy predicted by gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid‐enhanced T1 mapping magnetic resonance imaging - Liu, Jiao (JGH Open, 2021)
BACKGROUND AND AIM: Studies have found that gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA)‐enhanced T1 mapping magnetic resonance imaging (MRI) could assess liver fibrosis, cirrhosis, and function with high effectiveness. The aim of this study is to explore the efficacy of MRI in predicting the safety of hepatectomy. METHODS: Forty‐nine patients who underwent liver resection were recruited. Gd‐EOB‐DTPA‐enhanced MRI examination was performed 1 week before surgery, and the rate of T1 relaxation time reduction (ΔT1(20min)%) of liver parenchyma was calculated. Posthepatectomy liver failure (PHLF) was defined by the “50–50 criteria” and International Study Group of Liver Surgery (ISGLS) classification, respectively, and posthepatectomy complications (PHC) were defined by the Clavien‐Dindo grading system. The effectiveness of ΔT1(20min)% in predicting the occurrence of PHLF and PHC was analyzed. RESULTS: The area under the curve (AUC) for ΔT1(20min)% predicting PHLF meeting “50–50 criteria” was 0.957, with a cutoff value of 0.497, sensitivity of 100%, and specificity of 89.1%. The AUC for predicting ISGLS grade B/C (severe) PHLF was 0.84, with a cutoff value of 0.5232, sensitivity of 63.6%, and specificity of 92.6%. The AUC for predicting PHC of Clavien‐Dindo grades 3–5 (severe) was 0.882, with a cutoff value of 0.5646, sensitivity of 87.5%, and specificity of 75.8%. Univariate and multivariate analyses showed that ΔT1(20min)% < 0.4970 (P < 0.01) was an independent risk factor for the development of PHLF (50–50 criteria). Univariate and multivariate analyses showed that liver stiffness measurement and ΔT1(20min)% were risk factors for severe PHLF and severe PHC. CONCLUSIONS: Gd‐EOB‐DTPA‐enhanced T1 mapping MRI accurately predicts the safety of hepatectomy.